KESADARAN SEJARAH DAN NASIONALISME: PENGALAMAN INDONESIA - Aman Aman (Informasi, 2009)
The teaching of history, learning focus of diversity of human experience and understanding more about themselves as individual and member of society. Knowing your self means knowing that you can do; and since nobody knows what he can do untul he tries, the only clue to what man can do is what man has done. The value of history, then, is that it theachs us what man has done and then what man is. That history is more than the passage of events whose sequence may be memorized and that the past has continuing relevance for the presents. Most simply, we all live history, and not merely in the grand sense of wars, recessions, and political reformation. Rather, we live out the assumptions of our époque in the most mundane aspects of our daily lives. Key Word: history, history consciousness, and nationalism.